Football mania - the change in attitude towards football in Slovenia - Doupona, Mojca (Kinesiologia Slovenica, 2002)
The article deals with the attitude of inhabitants of Ljubljana and Maribor towards football. The historical, cultural and political circumstances that greatly influenced the shaping of the attitude towards football in Slovenia were taken in consideration. On the basis of a statistical research, the article tries to establish if there are statistically significant differences regarding the attitude towards football among the respondents from Ljubljana and Maribor, among people of Slovene descent and respondents with an ancestral background. The article also tries to establish if the appearance of the Slovene national football team at an important sports event like the EURO 2000 can statistically affect the attitude of people towards football. The article has been based on a research which covered 50 respondents from Ljubljana and 50 respondents from Maribor (investigated before the EURO 2000) and 50 respondents from Ljubljana (investigated after the EURO 2000), totally 150 subjects. The sample includes the variables of residence, nationality and attitudes towards football. Two factors Analysis of variance was used for establishing the differences between the selected variables. The research results show that inhabitants of Maribor have a much more positive attitude towards football than inhabitants of Ljubljana. A comparison between respondents of Slovene descent and those of non-Slovene descent proved that football is still considered the most popular sport. The respondents of non-Slovene descent have a distinctly more positive attitude towards football than the respondents of Slovene descent. The answers given by the respondents from Ljubljana, show that their attitude towards football changed significantly after the EURO 2000 in all the attitudes which proves the hypothesis that a positive attitude towards a sports discipline and good results in that discipline are greatly interconnected.
Keywords: Ljubljančani; Mariborčani; narodnost; nogomet; odnos do nogometa; raziskave; Slovenija